The Effect Of Using Technology as a Green Management Practice on the Organizational Environmental Performance at the International Arabic Islamic Bank (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The present study aims to show the effect of using technology as a green management practice on the organizational environmental performance at the International Arabic Islamic Bank in Jordan and to reveal implementation levels of technology usage and the level of organizational environmental performance at the International Arabic Islamic Bank. To achieve these objectives, the descriptive analytical survey method was used as a data collection tool (the questionnaire), which was distributed to a random sample consisting of (278) male and female employees of the International Arabic Islamic Bank  working in (45) branches, from which (200) forms were retrieved that were valid for analysis. For data analysis, appropriate statistical tests within the SPSS statistical analysis software were used. The results show a statistically significant effect for technology usage on the organizational environmental performance; technology usage explained about (42.1%) of the changes that occur on the organizational environmental performance; the level of the International Arabic Islamic Bank's use of technology as one of the practices of green management and the level of organizational environmental performance both came to a medium degree. The study recommends the necessity of evaluating the environmental performance of the bank in all fields (financial, economic, social, internal as well as external environment) and the need to select environmentally friendly customers and suppliers and focus on them, which increases the investment opportunity in industries that support the environment.
Keywords: Green Management; Environmental Performance; Technology; Regulatory; the International Arabic Islamic Bank